2003
DOI: 10.1177/0020764003494002
|View full text |Cite
|
Sign up to set email alerts
|

Inception Rates of Deliberate Self-Harm among Adolescents in West London

Abstract: The similarities between the Asian and white adolescents suggest that some common aetiological factors may be at play. The risk factors may be related to gender rather than ethnicity in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 5 publications
1
18
1
Order By: Relevance
“…Consistent with some previous work (e.g., Bhugra et al, 2003; Ross & Heath, 2002), a number of gender differences in NSSI were found suggesting unique vulnerabilities among adolescent girls. As past studies examining gender differences in NSSI have yielded mixed results, a careful examination of gender at different developmental periods may be important for elucidating differential patterns of NSSI behavior among boys and girls.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with some previous work (e.g., Bhugra et al, 2003; Ross & Heath, 2002), a number of gender differences in NSSI were found suggesting unique vulnerabilities among adolescent girls. As past studies examining gender differences in NSSI have yielded mixed results, a careful examination of gender at different developmental periods may be important for elucidating differential patterns of NSSI behavior among boys and girls.…”
Section: Discussionsupporting
confidence: 89%
“…Prevalence estimates from clinical samples are notably higher overall and reveal a similar developmental pattern; rates of NSSI are 2 to 3 times higher among adolescents (40–60%; Darche, 1990; DiClemente, Ponton, & Hartley, 1991) compared to adults (~21%; Briere & Gil, 1998). Some studies have reported that adolescent girls engage in NSSI more frequently than boys (Bhugra, Thompson, Singh, & Fellow-Smith, 2003; Ross & Heath, 2002). The evidence is conflicting, however, as other investigators have failed to find gender differences (e.g., DiClemente et al, 1991; Garrison et al, 1993; Gratz, Conrad, & Roemer, 2002; Hilt, Nock, et al, 2008).…”
mentioning
confidence: 99%
“…Nevertheless, compared with their white counterparts, impulsivity and the lack of regret in the act of attempting suicide make repetition more likely. 44,45 Crawford et al 46 found that Indians, Pakistanis, and Bangladeshis who were born in the United Kingdom or were…”
Section: Suicidal Behaviour In Asian Immigrant Youthmentioning
confidence: 99%
“…There has been a particular focus on South Asian women (Bhogal, Baldwin, Hartland, & Nair, 2006;Bhugra, Baldwin, Desai, & Jacobs, 1999), with Husain, Waheed, and Husain (2006) posing the question: ''Why do South Asian women feel the need to harm themselves?''. Cooper et al (2006) concluded that South Asian women aged 16-24 were significantly more likely to self-harm than White women of the same age, but Bhugra, Thompson, Singh, and Fellow-Smith (2003) found there were no differences between White and Asian adolescents in first incidents of self-harm reported to hospital. Most research has been based on people attending Accident and Emergency departments and other hospital services, especially those who have taken an overdose, suggesting a suicide attempt.…”
Section: Introductionmentioning
confidence: 99%